Mediating effect of self-efficacy on the relationship between Big Five personality and medication adherence in Chinese hypertensive patients: a national cross-sectional study - Du, Mingliang; Wu, Yibo; Wang, Boran; Jiang, Miao; Chen, Jiangyun; Hui, Hui (Frontiers in Psychology, 2024)
Objective The study aims to evaluate personality characteristics, self-efficacy, and medication adherence in Chinese patients with hypertension, while also investigating how self-efficacy mediates the relationship between personality traits and medication adherence. Methods This investigation included 787 Chinese patients diagnosed with hypertension, as reported in the “2021 China Family Health Index Survey Report.” The study employed several assessment tools such as a General Information Questionnaire, the Brief Big Five Inventory (BFI-10), the New General Self-Efficacy Scale (NGSES), and the Medication Adherence Rating Scale (MARS). Statistical analyses encompassed the Mann–Whitney U test, chi-square test, multiple logistic regression, Spearman’s rank correlation, standardized regression coefficients, and Bootstrap techniques. Results (1) Individuals with debt, who also possess high levels of self-efficacy, tend to adhere more consistently to their medication regimens. (2) An analysis of personality traits indicated that Extroversion,Conscientiousness and Openness positively influences self-efficacy,while Agreeableness and Neuroticism negatively impacts it. (3) Self-efficacy plays a mediating role in the indirect relationship between personality traits such as Extroversion and neuroticism and medication adherence. Conclusion In the context of Chinese adults, both self-efficacy and Extroversion positively influence medication adherence, whereas high levels of neuroticism adversely impact it. Furthermore, self-efficacy serves as a mediating factor in the linkage between personality traits and medication adherence.